2003
DOI: 10.1152/ajpheart.00098.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nephrectomy and captopril on autoregulation of cerebral blood flow in rats

Abstract: . Effect of nephrectomy and captopril on autoregulation of cerebral blood flow in rats. Am J Physiol Heart Circ Physiol 285: H1097-H1104, 2003. First published May 15, 2003 10.1152/ajpheart.00098. 2003.-The present study investigated the effect of circulating versus locally present renin on cerebral blood flow (CBF) and its autoregulation in rats. CBF was measured repetitively with the intracarotid 133 Xe injection method, whereas blood pressure was lowered to determine the lower limit of autoregulation. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…(54 ± 10 mmHg), our data are in close agreement to data published from other groups (Hossmann, 1994;Panerai, 1998;Pedersen et al, 2003;Tonnesen et al, 2005). Stating the results of Tonnesen et al (2005), we also found a sloped rather than a perfect horizontal autoregulative plateau.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(54 ± 10 mmHg), our data are in close agreement to data published from other groups (Hossmann, 1994;Panerai, 1998;Pedersen et al, 2003;Tonnesen et al, 2005). Stating the results of Tonnesen et al (2005), we also found a sloped rather than a perfect horizontal autoregulative plateau.…”
Section: Discussionsupporting
confidence: 93%
“…From the unstimulated cerebral blood flow recordings, the lower limit of autoregulation was calculated according to published procedures (Pedersen et al, 2003). In short, the lower limit was identified as the mean arterial blood pressure that corresponds to the intersection between two linear regression lines: one horizontal line above the lower limit (the plateau), and another line below the lower limit.…”
Section: Methodsmentioning
confidence: 99%
“…A post hoc analysis of the laser-Doppler data plotted as a function of cerebral perfusion pressure was used to delineate a discrete LLA for each subject using piecewise linear regression (17). The cohort LLA was 39 mmHg (28 -45 mmHg), which is consistent with precedent work in neonatal swine (12,16).…”
Section: Methodsmentioning
confidence: 56%
“…Pressure autoregulation and its lower limit were calculated as described by Pedersen et al (24). In brief, the lower autoregulatory limit was obtained from the intersection of two lines found by the least square technique, and a constraint was put on the horizontal line.…”
Section: Methodsmentioning
confidence: 99%